Overlap of female reproductive cycles explains shortened interclutch interval in a lizard with invariant clutch size (Squamata: Gekkonidae: Paroedura picta) - Weiser, Hana; Starostová, Zuzana; Kubička, Lukáš; Kratochvíl, Lukáš (Physiological and biochemical zoology, 2012)
Variable clutch size is unambiguously an ancestral state in reptiles. Only several lizard lineages have evolved so-called invariant clutch size, where all females lay just one or two eggs per clutch. This mode of reproduction is characteristic for geckos. In some gecko lineages, decreased fecundity in a single clutch is compensated by conspicuous shortening of interclutch intervals. The proximate mechanism of high clutch frequency in these geckos is not known. Here, we document that three subsequently laid clutches develop simultaneously in females of the Madagascar ground gecko (Paroedura picta). The extremely short interclutch intervals in this species-even as short as a week-thus could be attributed to the overlap of female reproductive cycles. Such overlap should be associated with altered female hormonal cycles. Based on measurements of hormonal levels, we suggest that cycles of estradiol and progesterone during reproductive cycles of females in P. picta are largely independent. Thus, in contrast to the presumable ancestral reptile state, higher levels of progesterone do not seem to interfere with vitellogenesis in this species. We discuss potential consequences of this derived mode of reproduction, such as possible simultaneous maternal transfer of nutrients and other yolk components to several subsequent clutches.
Keywords: Radioimmunoassay; Madagascar; Estradiol; progesteron; Female; Clutch Size; radioimunoanalýza; estradiol; velikost snůšky; Lizards; Reproduction; zvířata; Progesterone; Time Factors; ženské pohlaví; ještěři; Animals; Vitellogenesis; časové faktory; Madagaskar; rozmnožování; vitelogeneze